2012
DOI: 10.1097/inf.0b013e3182611d6b
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in the Middle Ear of Children With Recurrent or Chronic Otitis Media Is Associated With Bacterial Load

Abstract: The presence of bacteria, but not viruses, is associated with an increased inflammatory response in the middle ear of children with recurrent or chronic OM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
(36 reference statements)
2
12
0
Order By: Relevance
“…However, we can conclude that if respiratory viruses were present in MEF, they induce low proinflammatory responses. Consistent with our conclusion, Stol et al showed no association of viruses and changes in cytokine levels in chronic OM …”
Section: Discussionsupporting
confidence: 93%
“…However, we can conclude that if respiratory viruses were present in MEF, they induce low proinflammatory responses. Consistent with our conclusion, Stol et al showed no association of viruses and changes in cytokine levels in chronic OM …”
Section: Discussionsupporting
confidence: 93%
“…Elevation of IL-8 level is a marker for ongoing inflammation, which can be induced by bacterial infection and other injuries in the middle ear. 40 Our study showed that both bacterial infection and the presence of pepsin A were correlated with elevated IL-8 level in the middle ear. Studies in vitro have shown that exposure to cytokines such as IL-8 in human middle ear epithelium can up-regulate mucin expression.…”
Section: Discussionsupporting
confidence: 49%
“…40 Similarly, in animal studies, directly injecting a very small number of viable pneumococci into the middle ear resulted in elevated levels of IL-6, IL-8, and TNF in the middle ears. 40,45 As expected, we also found a strong correlation between bacterial infection and all 3 inflammatory cytokines, confirming the role played by bacterial infection on the level of inflammation in the ears and its independent contribution to middle ear inflammation (data not shown). However, positive pepsin or increased pepsin A levels did not show as strong an association with infection as we had initially hypothesized.…”
Section: Discussionmentioning
confidence: 97%
“…Viral replication induced epithelial and mucosal degradation, and the ensuing innate immune response yield diminished capacity to avert secondary bacterial infections. Recent clinical and experimental data suggest that influenza virus infection may exert its influence beginning in the URT by enhancing susceptibility to bacterial colonization (14, 47, 48) and increasing NP carriage density (36). …”
Section: Discussionmentioning
confidence: 99%